An Assessment of Mineral Contents in Fruits - Subedi, Thaneshwar (Prithvi Academic Journal, 2023)
Fruits are the important sources of minerals. The objective of this study is to determine the amount of ash, iron, calcium, magnesium and chloride in selected fruit samples: banana, grape, litchi, mango, papaya, pineapple, pomegranate and watermelon. A minimum value of ash content was 0.36 % for watermelon and maximum value was 1.705 for banana. The order of fruits with increasing percentage of iron is: watermelon (61.773002 ×10–5 %), and litchi, mango, grape, banana, pomegranate, papaya and pineapple (101.488695×10–5 %). A maximum amount of calcium (Ca) was found in the ash solution of fresh papaya (0.0375536%) and minimum amount of Ca was observed in banana (0.0037573%). The results showed that the mineral magnesium (Mg) was ranged from 0.0055316719% (for mango) to 0.031140771% (for papaya) with increasing order: mango, grapes, pineapple, water, pomegranate, litchi, banana and papaya. The experimentally recorded value of chloride as analyzed by argentometric titration using Mohr's method was observed in the order: grape (0.02127 %) < watermelon < papaya < mango < litchi < pineapple < banana < pomegranate (0.1790225 %). The observed results of this study showed that the mineral contents in ash solution of fruit samples are comparable to each other and with the reported values of various authors. The research outcomes will be beneficial for related researchers, fruit consumers and producers.